Interpersonal communication - Floyd, Kory (McGraw-Hill, 2011)
Demonstrates how effective interpersonal communication can make students' lives better. With consideration given to the impact of computer-mediated communication, this title helps students understand and build interpersonal skills and choices for their academic, personal, and professional lives